Tigecycline is the Most Effective against Multi-Drug Resistant Klebsiella pneumoniae Recovered from Burn Wound Infections in Two Hospitals in Al-Kut City, Iraq - Sadeq, Zahraa Eisaa; Lafta, Inam Jasim (Iraqi Journal of Science, 2024)
Klebsiella pneumoniae is among the most frequent microorganisms isolated from infections of burn wounds. This cross-sectional study aimed to investigate the distribution of multi-drug resistant (MDR) K. pneumoniae in two burn hospitals and the antibiotic resistance profile in different burn regions of the same patient. It was performed in two hospitals (Al-Zahraa and Al-Karama) in Al-Kut, Iraq, between January and May 2022. Totally, 100 burn swabs were collected from 40 patients of both genders suffering from burn wound infections, with ages ranging between 3 and 50 years. Klebsiella pneumoniae were isolated and identified using conventional methods followed by VITEK®2 system and confirmed via polymerase chain reaction targeting the gapA gene. Then, the antimicrobial susceptibility pattern was studied by the VITEK®2 system. Of the 100 burn wound swabs, 20 isolates were K. pneumoniae. Fifty five percent (11 out of 20) of K. pneumoniae isolated in the current study were MDR and 35% of the isolates had the extended spectrum beta-lactamase (ESBL) which is the main antibiotic resistance mechanism. Furthermore, the bacteria isolated from different burned areas of the same patient showed variable pattern of antibiotic susceptibility. To conclude, K. pneumoniae contaminating the burn wards in the Iraqi hospitals are mostly MDR, against which tigecycline is the most effective antibiotic.